The Influence Of Geometrical Dimensions On Electromechanical Performance In Stretchable Circuit - Omar, Ghazali; Salim, Mohd Azli; Masripan, Nor Azmmi; A Hamid, Husna; Mohd Yunos, Afiqah (Penerbit Universiti Sains Malaysia, 2020)
Stretchable conductive ink (SCI) had been extensively studied for fabricating stretchable electronic devices. In this study, silver conductive ink and thermoplastic polyurethane (TPU) were used as substrate. The ink was printed on the substrate using screen printing with different shaped patterns varied by the widths of 1 mm, 2 mm and 3 mm: (a) straight, (b) zig-zag, (c) square and (d) sinusoidal. The measurement of resistance was performed using four-point measurement during unloaded and loaded conditions of the shape pattern. This study revealed that width had influenced the resistivity in all shape patterns, where the narrow the width, the higher the resistance is. Comparative studies of electromechanical analysis of the shaped patterns had showed that a 3 mm width of zig-zag pattern had a better electromechanical performance by having stretchability to maximum of 7.78%. Straight and square shape patterns, however, exhibited the poor tolerate deformation as both failed to conduct electricity upon straining at the minimum elongation of 1.11%.